Branquitude e educação antirracista: diários de uma jornada - Vieira, Geovana Simões [UNESP]; Silva, Bruna Nascimento Rugerio [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
This work is the result of two trajectories that walk in parallel and intersect when the issues are about education, whiteness and anti-racist practice. Bruna and Geovana are class partners, graduates of the Licentiate in Art-Theatre course, and they seek, in the course of their journeys, to report through a logbook, their reflections and practical attempts to provide an anti-racist education with children, raise questions about of white identity (also known as whiteness or whiteness), they make self-analysis of their respective experiences, in order to understand the spaces in which they occupy and then elaborate transforming actions. Keywords: journey; anti-racist education; whiteness; experience.

Este trabalho é o resultado de duas trajetórias que caminham em paralelo e se intercruzam quando os assuntos são sobre educação, branquitude e prática antirracista. Bruna e Geovana são parceiras de turma, formandas do curso de Licenciatura em Arte-teatro, e buscam no decorrer de suas jornadas relatar por meio de diário de bordo, suas reflexões e tentativas práticas para proporcionarem uma educação antirracista com crianças, levantam questionamentos a respeito da identidade branca (nomeada também como branquitude ou brancura), fazem autoanálises de suas respectivas vivências, para assim compreenderem os espaços em que ocupam e então elaborarem ações transformadoras.
Whiteness and anti-racist education: diaries of a journey
Keywords: Educação; Identidade racial; Narrativas pessoais; Paisagens literárias